Existence of sign-changing solutions for a third-order boundary value problem with nonlocal conditions of integral type - Smirnov, Sergey (Topological Methods in Nonlinear Analysis, 2023)
We prove the existence of at least one sign-changing solution for a third-order nonlocal boundary value problem by applying Leray-Schauder Continuation Principle. To illustrate the applicability of the obtained results, we consider an example.